Perspektywy rozwoju ubezpieczeń obowiązkowych - Mogilski, Władysław Wojciech (Perspectives of the Development of Compulsory Insurances, 2008)
The duty of the insurance protection can be well-founded with definite social or economic reasons. Important is however, so that compulsory insurance be legal and peaceable with law. In the insurance law, the compulsory insurance then such, wherein the statutory law or the international treaty puts on the definite subject the duty of the conclusion of the insurance contract, qualifies the conditions of insurance protection and consequences of not realization of the duty of the insurance. Ali other are voluntary insurances. In Poland works at present about 80 different insurances treated as obligatory. In spite of the accepted legal definition, over half of them have legal defects. Some are even contradictory to the Constitution because they disturb citizens rights. The system of compulsory insurances demands the diligent settlement. The further development should be an object of the supervision of the legislative Minister of Finance, for the purpose of the co-ordination of each special law with generalities of the insurance legislation. The legislator should with the greater consideration and the consequence use tools of the constraint of the insurance. For the cohesion of future legal solutions one shows that it is necessary to make novel resolutions regarding compulsory insurances for the whole system of compulsory insurances in Poland.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1197, s. 262-268